Web-Based Advanced Traveller Information System for Minna Metropolis, Nigeria - Adeleke, O. O.; Idoko, S.; Kolo, S. S.; Anwar, A. R.; Sijuwola, O. O.; Akinola, O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Advanced Traveller Information System (ATIS) is used to provide accurate, integrated and comprehensive travel and traffic information to road users. The information helps in both pre-trip and en-route decision making. This study developed a web-based ATIS for Minna metropolis in Nigeria. The information provided is from both primary and secondary sources. The developed ATIS provides information on route guidance, available intercity transport services and hotels in the metropolis. It also allows users to determine both weather and traffic flow conditions. A component of the system makes provision for electronic fare payment and booking of trips and hotel accommodation. The deployment of the ATIS is a source of static and dynamic information.